1998
DOI: 10.1007/s004380050833
|View full text |Cite
|
Sign up to set email alerts
|

Oligomers of the Cdc7/Dbf4 protein kinase exist in the yeast cell

Abstract: Cdc7/Dbf4 protein kinase is required for the initiation of DNA replication in Saccharomyces cerevisiae. Cdc7/Dbf4 protein kinase is not a cyclin-dependent kinase (CDK), but is regulated in a similar fashion in that the Cdc7 kinase subunit is inactive in the absence of the regulatory subunit Dbf4. In contrast to what is known about CDKs, Cdc7/Dbf4 protein kinase is shown to be an oligomer in the cell in this report. Genetic data that support this claim include interallelic complementation between several cdc7ts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…In this case, the ability of two different alleles to form dimers may be the determinant of complementation. Interallelic complementation based on dimerization has been observed with Cdc7p (Shellman et al, 1998). However, our two-hybrid and coimmunoprecipitation tests were unable to detect interaction between Cdc28p monomers.…”
Section: Multiple Functions Of Cdc28p Affecting Mitotic Progression Acontrasting
confidence: 55%
See 1 more Smart Citation
“…In this case, the ability of two different alleles to form dimers may be the determinant of complementation. Interallelic complementation based on dimerization has been observed with Cdc7p (Shellman et al, 1998). However, our two-hybrid and coimmunoprecipitation tests were unable to detect interaction between Cdc28p monomers.…”
Section: Multiple Functions Of Cdc28p Affecting Mitotic Progression Acontrasting
confidence: 55%
“…Although heteroallelic combinations of Ala55Thr and Ile59Asn yielded highly polarized cells (Figure 4), indicating noncomplementation, other pairs of alleles displayed complementation for the enhanced cell polarity and G2/M-shift phenotypes (Figure 4; Table 2). This pattern of complementation suggested that Cdc28p might function as a dimer as had been observed for Cdc7p (Shellman et al, 1998). To test this possibility, the CDC28 ORF was cloned into bait-and-prey yeast two-hybrid expression vectors in each of two experimental systems.…”
Section: The Cdc28 Ecp Mutants Define Multiple Complementation Groupsmentioning
confidence: 87%
“…DDK or Dbf4 oligomerization has been suggested previously (Shellman et al 1998;Matthews et al 2012). Furthermore, tandem BRCT domains form dimers that bind phospho-S/T motifs (Caldecott 2003;Rodriguez and Songyang 2008), and intermolecular dimerization between BRCT domains has also been described for the DNA repair proteins XRCC1 and Ligase III (Cuneo et al 2011).…”
Section: Models For Rad53 Binding To Dbf4mentioning
confidence: 88%
“…One-hybrid and two-hybrid assays: Liquid culture b-galactosidase and X-Gal assays were done as previously described (Shellman et al 1998;Dohrmann et al 1999).…”
Section: Methodsmentioning
confidence: 99%